Banking crisis in Central and Eastern Europe New credit perspective - Pospíšil, Martin; Hnilica, Jiří, 1976-; Špička, Jindřich, 1981-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2010)
In the recession times of the last two years, it is of a good interest to test the behaviour of commercial banks. In this thesis, I link the Stiglitz-Greenwald theory of credit rationing with microeconomic Central and Eastern Europe banking group data over years 2007 and 2009. For the deeper understanding of the credit side of the banking system it is however necessary to analyse banks from a more detailed perspective. Therefore, a significant part of the thesis is focused on the financial analysis of commercial banks' balance sheets. This analysis then allows finding the reasons why and when did the banks change their behaviour, their approach to clients, businesses when supplying credits. I also analyse various steps that the banks took to deal with the financial crisis. While the crisis started as primarily financial, it was due to the information asymmetry/uncertainty (when banks could not screen and understand their clients properly) that this crisis turned into an economic one. The thesis is divided into two subparts. The first one describes the Greenwald-Stliglitz monetary paradigm and analyses it with respect to Czech microeconomic data. The second part extends this analysis and focuses on the balance sheet development and credit behaviour of five biggest banking groups in the CEE. The result of this thesis can help to understand banks' approach to their clients, the monetary transmission mechanism, and the behaviour of the banking system in general.
Vedoucí práce: Jiří Hnilica
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2010
Rok obhajoby 2010
Keywords: international Management [obor dipl. práce]; diplomové práce; master's theses